COMPETENCY-BASED PASSION AND VALUE-BASED DEDICATION INDONESIAN ENTREPRENEURIAL PERSISTENCE AMID THE COVID-19 PANDEMIC - Husni, Fransiskus Xaverius; Suwarto, F X; Hariandja, Evo Sampetua; Tan, Jacob Donald (Universitas Multimedia Nusantara, 2023)
Abstract- In 2021, Indonesia's national income significantly decreased as a result of the COVID-19 pandemic. During that time, a large number of SMEs failed, although some managed to recover. The goal of the research is to acquire experience with entrepreneurial tenacity and turn it into explicit knowledge. Using Interpretative Phenomenological Analysis to analyse the persistence experiences of ten entrepreneurs with COVID-19 bounce-back experience. Informants are selected with purposive sampling based on multiple perspective approach. In-depth interviews were conducted for data collection. Two stages of coding is used for theming process, which are followed by conceptualization process. Confirmation of notions is achieved by elaborate coding. Research indicate that the drivers for the perseverance of Indonesian entrepreneurs amidst the COVID-19 pandemic can be attributed to Competencies-based passion and Value-based dedication. Entrepreneurs persevere because they are passionate about their industry and have faith in their ability to thrive. Another motivator is their commitment to enduring because of the beliefs or principles they cherish.Entrepreneurs that are persistent will have greater opportunities, particularly since they would have more time to become familiar with the challenges posed by COVID-19. The effects of COVID-19 are also diminishing over time. It is their competency- based passion and value-driven determination that enable entrepreneurs to persevere in the face of adversity. Perseverance and resilience must be combined when business transformation is mandatory. Keywords: COVID-19 Pandemic; Indonesia; Competency-Based Passion; Persistence Experience; Value-Based Dedication